Green Supply Chain Management Drivers and Barriers: A Comparison of a Global and African View - Ethel Tembo MWANAUMO; Bupe Getrude MWANZA; Levy SIAMINWE (Communications of International Proceedings, 2022)
Green Supply Chain Management (GSCM) has received increased attention in recent years from Governments, Manufacturers and Academics both in the developed and developing world. The developed world has made progress in finding ways to mitigate environmental effects of industry activities while the developing world is striving to move from traditional Supply Chain Management to GSCM. The objective of this study was to make a comparison of the Global and Africa view of Drivers and Barriers to GSCM with the aim of identifying what is unique to the African continent. This would provide insight in how to strategically approach the African situation and to provide direction for future research. This was achieved by carrying out a systematic Literature Review on Drivers and Barriers of GSCM practices both in the developed and developing world. Some of the identified common Drivers include Government Regulations and Legislation, customer needs for green products, the need for standard quality certification by companies, the need to reduce harmful effects to the environment and company need for a green image locally and globally. Among the similarities on Barriers to GSCM practices were lack of resources, lack of government support, lack of technological knowhow, lack of communication among stakeholders in the Supply Chain and resistance to change. It was found that while common Drivers and Barriers exist, corruption was identified as a unique barrier to Africa. Specific interventions to discourage corruption as a Barrier to GSCM practices in Africa need to be explored to improve GSCM implementation.
Keywords: Barriers; Drivers; Green Supply Chain Management.; Africa